Sustainability reporting in the light of the EU’s new directive : Double materiality analysis for a health technology company - Silaskivi, Emma (My University, 2024)
Sustainability reporting has evolved drastically, especially in recent years, moving from voluntary reporting to legal obligations. Businesses must now report on sustainability in accordance with the new EU Directive on corporate sustainability reporting (CSRD). This directive requires companies to report on their sustainability according to a double materiality perspective. However, firms face challenges in understanding what is double materiality, and which impacts, risks and opportunities regarding sustainability are relevant for them. Increasing demand for this sustainability information from various stakeholders has highlighted the growing need to understand the nature of double materiality and context of sustainability issues specific to different sectors. Currently, the foundation of sustainability reporting lies in materiality, which has evolved into a concept of double materiality under the new EU directive. Double materiality means that businesses are required to report not only on their environmental and social impacts, but also on how these impacts may affect it financially. This linkage integrates both impact and financial materiality and a holistic understanding the whole value chain in the same process. By first mapping their value chain, organisations can better understand how different issues impact various stakeholders. This approach helps identify issues the company influences as well as impacts that create either risks or opportunities for the company. Since the study is commissioned, the primary focus and perspective are on the health technology industry. The research employed a constructive research approach with qualitative techniques, using semi-structured interviews with internal stakeholders and the examination of secondary data form voluntary standards and competitor reports. This study focused on a single case. Findings align with literature and highlight that mandatory EU reporting forces companies to improve their sustainability reporting. Social impacts were identified the most relevant issues for a health technology company, but also environmental issues, particularly those related to the circular economy, were recurring. The research provides insights on material sustainability impacts risks and opportunities for a health technology company and a devised tool that can be utilized by companies beyond the health technology sector to conduct a double materiality assessment. The tool considers sector specific sustainability issues while understanding impact of stakeholder sustainability throughout the value chain. Moreover, the study provides valuable information on the identification of relevant sustainability issues across stakeholders and company operations enabling the development of sustainability reporting and strategy.

Vastuullisuusraportointi on kehittynyt viime vuosina merkittävästi. Aiemmin vapaaehtoisesta raportoinnista on siirrytty lakisääteiseen raportointiin, mikä tarkoittaa, että yritysten on nyt raportoitava vastuullisuudestaan Euroopan Unionin kestävyysraportointidirektiivin mukaisesti. Tämä standardi vaatii yrityksiä raportoimaan sekä ympäristö- että sosiaalisista vaikutuksistaan sekä siitä, miten nämä vaikutukset voivat vaikuttaa yrityksen taloudelliseen tilanteeseen. Tätä kutsutaan kaksoisolennaisuudeksi. Monet yritykset kohtaavat haasteita ymmärtää, kuinka kyseinen arviointi tulisi suorittaa ja mitkä kestävään kehitykseen liittyvät vaikutukset, riskit ja mahdollisuudet ovat heille olennaisia. Sidosryhmien kasvava tarve vastuullisuustiedolle on korostanut tarvetta ymmärtää tätä kaksoisolennaisuuden periaatetta ja vastuullisuuskysymysten merkittävyyttä eri toimialoilla. Tällä hetkellä vastuullisuusraportointi perustuu olennaisuuteen, joka on kehittynyt uuden EUdirektiivin myötä ottamalla käyttöön kaksoisolennaisuuden periaatteen. Tämä lähestymistapa yhdistää vaikutusten ja taloudellisen olennaisuuden merkityksen koko arvoketjussa. Ensimmäinen askel on arvoketjun kartoitus, joka auttaa yrityksiä ymmärtämään paremmin, miten erilaiset tekijät vaikuttavat eri sidosryhmiin. Tämän jälkeen yritykset voivat tunnistaa ne vastuullisuusasiat, joihin niiden toiminta vaikuttaa, sekä mahdolliset taloudelliset riskit ja mahdollisuudet. Tutkimuksen fokus on terveysteknologiateollisuudessa. Tutkimuksessa käytetään konstruktiivista tutkimusotetta ja laadullisena menetelmänä hyödynnetään puolistrukturoituja haastatteluja sekä sekundäärilähteistä kerättyjä vastuullisuusstandardeja ja kilpailijoiden vastuullisuusraportteja. Tutkimus keskittyy yhteen tapaukseen. Yleisesti tutkimustulokset ovat linjassa kirjallisuuden kanssa ja korostavat sitä, että EU:n raportointivelvoite pakottaa yritykset kehittämään vastuullisuusraportointiaan. Sosiaaliset vaikutukset todettiin terveysteknologia-alalle olennaisimmaksi, mutta myös ympäristökysymykset, erityisesti kiertotalous, tulivat esille tuloksissa. Tutkimus osoittaa, että terveysteknologiayrityksille voidaan tunnistaa merkittäviä vaikutuksia, riskejä ja mahdollisuuksia vastuullisuuden näkökulmasta. Lisäksi tutkimus esittelee kehitetyn työkalun, jota voivat hyödyntää myös muut kuin terveysteknologia-alan yritykset kaksoisolennaisuusanalyysin tekemiseen. Työkalussa huomioidaan toimialakohtaiset vastuullisuuskysymykset ja arvioidaan sidosryhmien vastuullisuusvaikutukset koko arvoketjussa. Tutkimus korostaa myös olennaisten vastuullisuusteemojen tunnistamisen merkitystä niin sidosryhmille kuin yritykselle itselleen. Tämä voi edesauttaa vastuullisuusraportoinnin ja - strategian kehittämistä myös tulevaisuudessa.
Keywords: CSRD, double materiality, double materiality assessment, health technology, sustainability reporting, kaksoisolennaisuus, kaksoisolennaisuusanalyysi, kestävyysraportointidirektiivi, vastuullisuusraportointi, terveysteknologia